The Role of Technology in the COVID-19 Pandemic Era: A lesson learned from Indonesia in Increasing Access to Legal Aid - Arsa Ilmi Budiarti; Dio Ashar Wicaksana; Nanda Oktaviani (Advanced Studies on Socio-Economy Development, 2023)
The COVID-19 Pandemic has increased the prevalence of legal problems, such as criminality, massive unemployment, domestic violence, and inequality in society. This condition further causes legal aid services to be progressively needed. Meanwhile, many people still do not know about free legal assistance from the Government through legal aid organizations or lawyers through pro bono legal services. Moreover, the global policy encouraging social and physical distancing makes it difficult for people to access the legal aid service provider office directly. Therefore, an accessible and comprehensive platform that provides information and free legal aid services is very much needed in this COVID-19 situation for justice seekers—as internet use is growingly massive during the pandemic. This article shows why and how technology expands access to legal Aid, explained through interviews with legal aid providers and desk review. With the Indonesian case, this study argues that optimizing technology's role does not necessarily involve creating a massive and complicated technological system but rather ensuring the current or existing platform can fulfill justice seeker needs and be inclusively accessible to vulnerable groups. Legal needs assessment and a multistakeholder approach must be encouraged sustainably to ensure the platform can achieve those goals. Keywords: Access to Justice, Covid-19 pandemic, Free Legal Aid, Technology, Vulnerable Groups.